The Anthropocene: a conspicuous stratigraphical signal of anthropogenic changes in production and consumption across the biosphere. Issue 3 (14th March 2016) - Williams, Mark; Zalasiewicz, Jan; Waters, Colin N.; Edgeworth, Matt; Bennett, Carys; Barnosky, Anthony D.; Ellis, Erle C.; Ellis, Michael A.; Cearreta, Alejandro; Haff, Peter K.; Ivar do Sul, Juliana A.; Leinfelder, Reinhold; et al.
Abstract: Biospheric relationships between production and consumption of biomass have been resilient to changes in the Earth system over billions of years. This relationship has increased in its complexity, from localized ecosystems predicated on anaerobic microbial production and consumption to a global biosphere founded on primary production from oxygenic photoautotrophs, through the evolution of Eukarya, metazoans, and the complexly networked ecosystems of microbes, animals, fungi, and plants that characterize the Phanerozoic Eon (the last ∼541 million years of Earth history). At present, one species, Homo sapiens, is refashioning this relationship between consumption and production in the biosphere with unknown consequences. This has left a distinctive stratigraphy of the production and consumption of biomass, of natural resources, and of produced goods. This can be traced through stone tool technologies and geochemical signals, later unfolding into a diachronous signal of technofossils and human bioturbation across the planet, leading to stratigraphically almost isochronous signals developing by the mid‐20th century. These latter signals may provide an invaluable resource for informing and constraining a formal Anthropocene chronostratigraphy, but are perhaps yet more important as tracers of a biosphere state that is characterized by a geologically unprecedented pattern of global energy flow that is now pervasively influenced and mediated by humans, and which is necessary for maintaining the complexity of modern human societies. Key Points: Humans refashioning relationship between production and consumption in the biosphere Biosphere characterized by pattern of global energy flow pervasively influenced by humans Changes consistent with the biosphere entering a new stage of its evolution